U-Shaped Association Between Serum Uric Acid Level and Hypertensive Heart Failure: A Genetic Matching Case-Control Study - Xu, Hongxuan; Wang, Quan; Liu, Yunqing; Meng, Lingbing; Long, Huanyu; Wang, Li; Liu, Deping (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background: Heart Failure (HF) is a global pandemic and lays an added burden on public healthcare. Previous studies indicated that high and low serum uric acid levels are associated with worse outcomes in many diseases. Reduced serum uric acid may not result in a better outcome. Methods: A comparative, matched cross-sectional study design was implemented. The matching variables were age, sex, BMI, BP, and histories of CKD, CVD, diabetes mellitus, stroke, hyperlipidemia. We reviewed the electronic medical records to identify patients diagnosed with hypertension or hypertensive heart failure (HHF) admitted to Beijing Hospital's cardiology department. Results: The median age of the two groups after matching are 71. There are 55.6% males in the hypertension group and 53.8% in the heart failure group. Univariate logistic regression analysis showed that UA's quadratic term is significant (OR=1.00, 95% CI 1.00 to 1.00; P =.03), which indicated a u-shaped relationship between hypertension and HHF. FBS (OR= 0.22, 95% CI 0.05 to 0.95, p=.07) and HDL (OR= 1.23, 95% CI 1.00 to 1.54, P=.05) were insignificant but close. Conclusion: Our results supported that both low and high uric acid levels were predictive of hypertensive heart failure. Besides, high-density lipoprotein cholesterol and fasting blood sugar were also associated with hypertensive heart failure. Low-density lipoprotein cholesterol was not associated with hypertensive heart failure.